Growth rate, leaf:stem ratio and height in crotalaria (Crotalaria juncea L.) planted at different densities (Agro Productividad, 2022)
Objetive: To evaluate the growth rate, leaf:stem ratio and height of crotalaria plants (Crotalaria juncea L.), cultivated at different densities, in the dry tropics of the state of Guerrero, Mexico.Desing / Methodology / Approach: The treatments were: four planting densities at 400,000, 200,000, 100,000 plants ha-1 and trickling. A growth analysis was also evaluated at 30, 38, 45, 52, 60, 68 and 75 days of growth, including that the pod was fully developed. The variables evaluated were: growth rate, leaf:stem ratio and plant height.Results: The best growth rate was found at a density of 400,000 plants ha-1, at 75 days of development, with 577 kg DM ha-1 d-1; similar to plant height, which at this density presented 281 cm. Contrary to the leaf:stem ratio, which was greater than 30 days. Regardless of age, a descending behavior was found in the following order: 100,000 ˃ chorrillo ˃ 200,000 ˃ 400,000 plants ha-1 with 0.65, 0.60, 0.59 and 0.55 (p < 0.05).Study Limitations / Implications: This study is essential for future research because these variables have not been evaluated in this crop; being important for forage production.Findings / Conclusions: It is recommended to sow at a density of 400,000 plants ha-1, finding a higher leaf:stem ratio at 30 days of development and a plant height at day 75, when pod production also begins